Communication Strategy of Kasepuhan Sinar Resmi Community in Maintaining Local Varieties for Strengthening Leuit (Village Barns) - Mas Ayu Ambayoen; Bayu Adi Kusuma; Resya Eka Pratiwi (Socio-Economics/Agribusiness Department, 2018)
Village food barn is one concept of food security based on local wisdom that is able to maintain the stability of food supply of the community. Leuit (barns) for Kasepuhan Sinar Resmi Community is a tradition of harvesting of rice that still exists today. The harvests stored in Leuit come from local varieties that are still preserved its authenticity. There are about 68 local varieties that are still cultivated by the Kasepuhan community. The results of this study indicate that there is a communication strategy conducted by Kasepuhan Sinar Resmi community in maintaining local varieties and Leuit sustainably. The communication strategy is reflected in the oral tradition from generation to generation. As a society, that still follows the paternalistic culture; the role of traditional leader is very dominant. In addition, customary values and norms are still well maintained, such as taboo culture (pamali), selling crops and the sharing of local varieties grown to maintain the existence of Leuit sustainability and their local genetic resources.